2020
DOI: 10.1063/1.5139416
|View full text |Cite
|
Sign up to set email alerts
|

Lateral transport in silicon solar cells

Abstract: We investigate lateral charge carrier transport in crystalline silicon solar cells. Under typical operation illumination of high efficiency solar cells, a significant population of electrons and holes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Indeed, restricting the rear metal contact fraction increases the series resistance due to the rear contact resistance ( R S,contact ≈ ρ c /metal contact fraction) and the lateral resistance in the n‐Si substrate ( R S,lateral ). [ 36 ] Note that conversely, as the whole rear side was in contact with the metallic measurement chuck, R S,finger is not expected to contribute to R S,total (similarly to a “busbarless” measurement) for any finger width. The increase in series resistance is obvious in Figure a,b shows the series resistance extracted from two‐diode fits of the data, confirming this interpretation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, restricting the rear metal contact fraction increases the series resistance due to the rear contact resistance ( R S,contact ≈ ρ c /metal contact fraction) and the lateral resistance in the n‐Si substrate ( R S,lateral ). [ 36 ] Note that conversely, as the whole rear side was in contact with the metallic measurement chuck, R S,finger is not expected to contribute to R S,total (similarly to a “busbarless” measurement) for any finger width. The increase in series resistance is obvious in Figure a,b shows the series resistance extracted from two‐diode fits of the data, confirming this interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…We performed simulations using the framework developed in Haschke et al [ 36 ] to quantitatively evaluate how the different rear metallization patterns affect R S,contact and R S,lateral for different values of contact resistance from 0.1 to 0.4 Ω cm 2 . The range of variation is shown in Figure 3 as the orange areas.…”
Section: Resultsmentioning
confidence: 99%
“…They found the values of 140 and 33 mΩ cm 2 for the a‐Si:H(i + n)/TCO and TCO/Ag interfaces, respectively. Haschke et al [ 12 ] investigated the lateral charge carrier transport in HJT solar cells under typical operating illumination conditions comparing simulations and experimental results. They found that the coupling contact resistance needs to be low to benefit from lateral current flow in the silicon absorber and reported the values lower than 300 mΩ cm 2 for the p‐contacts in their devices.…”
Section: Resultsmentioning
confidence: 99%
“…This shows that in addition to ρ c also R sheet was sufficiently low using O 2 -rich ITO in combination with low-oxygen ITO interlayer. It is important to mention that lateral transport is not only provided by the TCO, but also by the silicon absorber [46]. The distribution of lateral transport between absorber and TCO is determined by ρ c and efficient coupling is only possibly with low ρ c .…”
Section: E Shj Solar Cells With Ito Stackmentioning
confidence: 99%